The RF in RFID : UHF RFID in practice. - Dobkin, Daniel Mark (Elsevier/Newnes, 2013)
This book explains how UHF tags and readers communicate wirelessly. It gives an understanding of what limits the read range of a tag, how to increase it (and why that might result in breaking the law), and the practical things that need to be addressed when designing and implementing RFID technology. Avoiding heavy math but giving breadth of coverage with the right amount of detail, it is an ideal introduction to radio communications for engineers who need insight into how tags and readers work. New to this edition: . Examples of near-metal antenna techniques . Discussion of the wakeup challenge for battery-assisted tags, with a BAT architecture example . Latest development of protocols: EPC Gen 1.2.0 . Update 18000-6 discussion with battery-assisted tags, sensor tags, Manchester tags and wakeup provisions The only book to give an understanding of radio communications, the underlying technology for Radio Frequency Identification (RFID)Praised for its readability and clarity, it balances breadth and depth of coverage New edition includes latest developments in chip technology, antennas and protocols.